Pengembangan Bahan Ajar Digital Pada Materi Panas Dan Perpindahannya Berbasis Kearifan Lokal Sumatera Selatan Kelas V SD - Mardiana, Ana; Suryani, Ida; H.M Lubis, Patricia; Ida; Patricia (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The development of digital teaching materials is currently very necessary in the world of education because elementary school students are surrounded by technology, even developing together with technology and local wisdom. Elementary school students who are in the concrete thinking range, in addition to requiring learning with concrete media, also need teaching materials to satisfy their curiosity and reduce boredom in learning. This study aims to produce a valid and practical digital teaching material product based on local wisdom on the material of heat and its transfer for class V of SD Negeri 04 Rantau Alai. This study uses the Research and Development research method using the ADDIE model (Analyze, Design, Development, Implementation and Evaluation). The results of this study obtained a score for an average media expert of 83% with the criteria "Very Valid", an average score for material experts of 88% with the criteria "Very Valid" Recapitulation of validation results of 85.5. Meanwhile, the results of the practicality of the product by 3 students and small groups obtained an average score of 86.55% with the criteria of "Very Practical" so that digital teaching materials based on the Material of Heat and Its Transfer Based on Local Wisdom are valid and practical for use in the learning process.